2001
DOI: 10.2307/3318727
|View full text |Cite
|
Sign up to set email alerts
|

Martingale Convergence and the Functional Equation in the Multi-Type Branching Random Walk

Abstract: A generalization of Biggins' Martingale Convergence Theorem is proved for the multi-type branching random walk. The proof appeals to modern techniques involving the construction of size-biased measures on the space of marked trees generated by the branching process. As a simple consequence we obtain existence and uniqueness of solutions (within a speci ed class) to a system of functional equations .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…The one-type branching random walk has received extensive treatment in the literature. The multitype extension has received less attention, but discussion of it can be found in Mode (1971), Biggins (1976), (1996), Bramson et al (1992), and Kyprianou and Rahimzadeh Sani (2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The one-type branching random walk has received extensive treatment in the literature. The multitype extension has received less attention, but discussion of it can be found in Mode (1971), Biggins (1976), (1996), Bramson et al (1992), and Kyprianou and Rahimzadeh Sani (2001).…”
Section: Introductionmentioning
confidence: 99%
“…The mean convergence of {W n i (λ)} for real λ was also discussed in Bramson et al (1992), Kyprianou and Rahimzadeh Sani (2001), and, rather briefly, in Biggins and Kyprianou (2004 (λ), where W i (λ) is the limit of the martingale {W n i (λ)} as n → ∞. The sequences {W n i (λ)} and {W n ij (λ)} converge on the set 2 introduced in Theorem 5.…”
mentioning
confidence: 96%
“…More generally, similar changes of measure for other types of branching processes have become increasingly common in the study of classical and modern branching processes; in particular, the reader is referred to Lyons et al [29] and Lyons [30]. Champneys et al [7], Harris and Williams [19], Olofsson [34], Athreya [2], Kyprianou and Rahimzadeh Sani [28], Biggins and Kyprianou [3], Engländer and Kyprianou [13] and Kuhlbusch [26] also provide further examples of their use.…”
Section: Spine Decompositions For Bbmmentioning
confidence: 99%
“…Also see Lyons et al [17,13,18] and other recent work based on these (examples are Kyprianou [14], Kyprianou and Sani [15], Athreya [1], Olofsson [19] amongst others) for similar spine based approaches in branching processes.…”
Section: The Spine Approach Martingales and Measuresmentioning
confidence: 99%
“…Git et al [4] presented alternative heuristic arguments based on birth-death processes to arrive at the expression (15). Using Euler-Lagrange techniques they showed that the specific path…”
Section: Large Deviations Heuristicsmentioning
confidence: 99%